2009
DOI: 10.1051/limn/09003
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of testate amoebae (Protists) inSphagnumpeatlands of eastern Poland: Vertical micro-distribution and species assemblages in relation to environmental parameters

Abstract: -The testate amoebae communities living among different species of mosses in Sphagnum peatlands in eastern Poland were studied. Sampling was done on a monthly basis from April to November [2005][2006][2007]. To assess the importance of the vertical distribution of testate amoebae within the mosses, each sample was cut into two parts: the upper living part (1-5 cm) and the lower dead part (5-10 cm). The highest species richness occurred in hollows dominated by Sphagnum angustifolium, Sphagnum flexuosum and Spha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
4
24
1
Order By: Relevance
“…A. flavum, Heleopera sphagni, and H. papilio together represented between 57% ("bog") and 88% ("fen") of the total community in the upper segments, but much less in the intermediate and lower segments. Thus in agreement with previous studies [25,34,35,39,54], mixotrophic species largely dominated the community in the upper segments, while heterotrophic species (e.g., P. griseola or The vertical micro-distribution of testate amoebae in Sphagnum reflects some gradients such as light, temperature, oxygen, and prey organisms [35,53]. A vertical niche separation among co-generic or otherwise closely related species also appeared in both sampling areas (e.g., the Amphitrematidae Archerella and Amphitrema, and the Hyalospheniidae Nebela, Hyalosphenia, and Physochila).…”
Section: Vertical Micro-distributionsupporting
confidence: 94%
See 1 more Smart Citation
“…A. flavum, Heleopera sphagni, and H. papilio together represented between 57% ("bog") and 88% ("fen") of the total community in the upper segments, but much less in the intermediate and lower segments. Thus in agreement with previous studies [25,34,35,39,54], mixotrophic species largely dominated the community in the upper segments, while heterotrophic species (e.g., P. griseola or The vertical micro-distribution of testate amoebae in Sphagnum reflects some gradients such as light, temperature, oxygen, and prey organisms [35,53]. A vertical niche separation among co-generic or otherwise closely related species also appeared in both sampling areas (e.g., the Amphitrematidae Archerella and Amphitrema, and the Hyalospheniidae Nebela, Hyalosphenia, and Physochila).…”
Section: Vertical Micro-distributionsupporting
confidence: 94%
“…Owing to ecological gradients and the preservation of their shells in peat and sediments, these protists are useful proxies in paleoenvironmental and ecological studies of peatland and lakes [6,11,43]. In Sphagnum bogs, testate amoeba community composition is generally strongly correlated to surface wetness conditions (mostly assessed by the water table depth (DWT)) and water chemistry [3,39,48,59].…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentrations of phosphate and ammonia may favor the occurrence of bacteria in aquatic environments, because these organisms are able to absorb these soluble ions, which are excreted by zooplankton (Pinto-Coelho et al 1997;Torres et al 2007). As a result, the higher bacterial biomass leads to an increase in the supply of food resources, as they represent important food items in the diet of many testate amoebae (Gilbert et al 2000;Mieczan 2009). …”
Section: Discussionmentioning
confidence: 99%
“…TA species richness is dependent on moss species identity, geographical location, sampling strategy (length of stem removed, number of samples and number of sampled mosses) and moss moisture (Bonnet, 1973). In the terrestrial mosses, Nguyen-Viet et al (2004, 2007a found nine species in T. muralis (Besanç on, France) and 23 species in B. indica (Hanoi, Vietnam), while Mieczan (2009) identified 45 TA taxa in the semi-aquatic mosses (Sphagnum). For these reasons, it is difficult to compare diversity of the TA community among different ecotoxicological studies.…”
Section: Study Sites Metal Trace Elements Accumulation and Ta Diversmentioning
confidence: 99%